2014
DOI: 10.1902/jop.2014.130654
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation Levels and Total Oxidant/Antioxidant Status in Serum and Saliva From Patients With Chronic and Aggressive Periodontitis. Oxidative Stress Index: A New Biomarker for Periodontal Disease?

Abstract: Background: In this study, levels of malondialdehyde (MDA), which is a significant product of lipid peroxidation (LPO), total oxidant status (TOS), total antioxidant capacity (TAOC), and the oxidative stress index (OSI), a novel value as a marker of periodontal disease activity, are investigated in serum and saliva from patients with chronic (CP) and generalized aggressive (GAgP) periodontitis. Methods: A total of 98 patients (33 with CP, 35 patients with GAgP, and 30 periodontally healthy controls) enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
149
2
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(178 citation statements)
references
References 44 publications
24
149
2
3
Order By: Relevance
“…Attachment loss was significantly more in patients of GP study group. Our results were in correlation with the results obtained by Baltacıoğlu et al, 18 who also reported similar findings in their study. In a prospective study, Akalin et al 14 investigated the MDA levels and TOS values in saliva, serum, and gingival crevicular fluid (GCF) of the CP patients.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Attachment loss was significantly more in patients of GP study group. Our results were in correlation with the results obtained by Baltacıoğlu et al, 18 who also reported similar findings in their study. In a prospective study, Akalin et al 14 investigated the MDA levels and TOS values in saliva, serum, and gingival crevicular fluid (GCF) of the CP patients.…”
Section: Discussionsupporting
confidence: 94%
“…From the results, the authors concluded that in the pathology of periodontitis, a significant role is played by elevated TOS and decreased TAOC. 18 On comparing the mean salivary MDA, TOS, TAOC, and OSI levels in between the three study groups, significant results were obtained (Tables 2 and 3). Similar results were reported in the past literature.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…1 Oxidative stress (OS) promotes the pathophysiological progression of periodontal disease by triggering local and systemic inflammatory responses. 2,3,4,5 Hyperlipidemia, i.e., elevated serum lipid levels, is thought to cause imbalance in the production of highly reactive molecular species and antioxidant defenses, leading to increased OS and creating a proinflammatory state that predisposes subjects to infections. 1,6 Hyperlipidemia is a risk factor for atherosclerotic diseases by causing hyperactivity of white blood cells, 7 and this hyperactivity leads to an increase in production of reactive oxygen species (ROS) and lipid peroxidation.…”
Section: Müge Lutfioğlu (A)mentioning
confidence: 99%